For Better Quality and More Integrated Primary Health Care Services through Harnessing the Private Sector in Sindh Province : Options Paper - World Bank Group (World Bank, Washington, DC, 2019)
Achieving universal health coverage (UHC) in Pakistan, as in most countries, will require strengthened collaboration between the public and private sectors, as the public sector often does not have the flexibility nor the fiscal space to grow service delivery capacity at sufficient pace and quality. However, successful partnering with the private sector through various forms of contracting and service agreements including public-private partnerships (PPPs), requires the appropriate analysis and identification of the gaps in service provision. To that end, this study aims to assist the government of Sindh (GoS) in identifying opportunities to engage the private health sector more effectively, to help provide affordable, quality primary health care (PHC) services to the urban poor whilst also creating evidence for the better integration of the private health sector in health service delivery. As part of the initial phase of this advisory work, and operating within a limited time-frame and funding environment, this policy note presents the initial set of observations and recommendations, based on the information collected via questionnaires and informant interviews, as well as secondary data or existing studies.